PENINGKATAN MOTIVASI DAN PRESTASI BELAJAR MELALUI PENGGUNAAN MEDIA AUDIO VISUAL DALAM PEMBELAJARAN PENDIDIKAN AGAMA KATOLIK PADA SISWA KELAS VIIB DI SMP KATOLIK AMBON - Reresi, Marsianus; Sermatang , Petrus C.R. (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STPAK St. Yohanes Penginjil Ambon, 2022)
This study aims to examine the increase in motivation and learning achievement through the use of audio-visualmedia in learning Catholic religious education in class VIIB students at Ambon Catholic Middle School. This research is very relevant to improving the quality of learning. The focus of this Classroom Action Research Action research is to find out how to increase motivation and learning achievement through the use of audio- visual media in learning Catholic religious education in class VIIB students at Ambon Catholic Middle School. The data collection technique used in this study was by using tests and observations from each cycle which were then analyzed descriptively quantitatively using percentage (%) and qualitative analysis techniques. Based on data analysis it was found that the use of audio-visual learning media became a learning medium that could increase learning motivation and learning achievement in learning Catholic Religious Education for class VIIb students of Ambon Catholic Middle School.